Molecular Analysis of Acquired Tamoxifen Resistance in Breast Cancer Cell Line - Abachi, Mansour; Salati, Monir; Araghi, Shahram; Shirkoohi, Reza; Eslamifar, Ali (Asian Pacific Journal of Cancer Biology, 2017)
Background: Tamoxifen is an FDA approved drug for the prevention and the treatment of breast cancer, but its therapeutic benefit is limited by the development of drug resistance. Many Studies suggest that a basic biological difference exists between tumors with acquired tamoxifen resistance and those with intrinsic resistance to the drug. However the reasons why human mammary tumors become resistant to tamoxifen therapy are mainly unknown. Changes in gene expression may occur as cells acquire resistance to tamoxifen. A better understanding of gene expression alterations associated with tamoxifen resistance will facilitate circumventing this problem. Methods: We undertook a comparative gene expression analysis of tamoxifen-sensitive (MCF7 and T47D) and acquired tamoxifen-resistant human breast cancer cell lines (T47D tamoxifen resistant) in vitro models using Real-time PCR, to analyze differential gene expression. These genes were functionally linked to 4 major groups named as ER signaling/cell cycling, EGFR signaling, cancer stem cell (CSCs) and apoptosis. Results: Our results have been widely demonstrated that the altered expression of some genes involved in apoptosis, EGFR signaling, CSCs and Cell cycle-independent expression of estrogen receptor such as ESR1, TP53, CDKN1B, Casp3, CD44, CD24, BAX, Bcl2, Her2, and PTEN in T47D tamoxifen resistant cell line can be resulted in drug resistance in long-term treatment. Conclusions: Our findings correspond with the results of many earlier studies indicated tamoxifen resistance can be a result from combination of molecular mechanisms including Her2 activation, cell cycle progression out of ESR1 control, increased ratio of CSCs and inhibition of mitochondrial apoptosis.